Anda di halaman 1dari 25

# Notes on Differential geometry and relativity

## theory (Faber, 1983)

Robert B. Scott,1,2

1
Institute for Geophysics, Jackson School of Geosciences, The University of Texas at Austin,
Austin, Texas, USA
2
Department of Physics, University of Brest,
Brest, France

2
Chapter 1

curvature

1.1 Curves
Exercises I-1

## (t) = (a cos t, a sin t, bt).

p
ds = (x0 dt)2 + (y 0 dt)2 + (z 0 dt)2

= a2 + b2 dt (1.1)

Thus the length of the helix is 2 a2 + b2 .

## 2. Parabola (t) = (t, t2 /2).

Velocity, 0 (t) = (1, t).
Acceleration, 00 (t) = (0, 1).

3. (a) Note the typo in this question. It should read . . . and verify that

3
4

||0 (0)|| = V0 .
0 (t) = (V0 cos , V0 sin 32t),
0 (0) = (V0 cos , V0 sin ),
||0 (0)|| = V0 . (1.2)

3. (b)
The acceleration is:
00 (t) = (0, 32). (1.3)
The direction is in the negative ydirection and the magnitude is 32 perhaps
in [ft s2 ].

## 4. Particle of matter moves on the branch of a hyperbole:

(t) = (a cosh t, a sinh t).
with a > 0.
Double check claim:
x2 y 2 = (a cosh t)2 + (a sinh t)2
 
2 exp (2 t) + exp (2 t) + 2 exp (2 t) + exp (2 t) 2
=a
4 4
2
=a . (1.4)
Velocity:
0 (t) = (a sinh t, a cosh t).
Acceleration:
00 (t) = (a cosh t, a sinh t) = (t).
The force will be proportional to the acceleration by Newtons second
law. The acceleration vector is identical to the position vector, and hence
proportional to the distance from the origin.

## 5. The curve is the parabola, (t) = (t, t2 /2). It cannot be reparameter-

ized in terms of arc length. Using the chain rule it was derived that
1
k(t) = .
(1 + t2 )3/2
Robs notes on Faber 5

## (a) Find the equation of the osculating circle at (0).

The curvature k(t) is the inverse of the radius of the osculating circle, c.f.
p. 8. So the radius of the circle is
1
= (1)3/2 = 1.
k(0)
By symmetry the centre of the circle lies on the yaxis. The curve bends
upward (see Problem 2), so the centre is a y = 1. So the equation is

x2 + (y 1)2 = 1.

## (b) Find the equation of the osculating circle at (2).

We must find the vector normal to the curve. The unit normal is N(s),
which is
1
N(s) = T0 (s)/k(s) = (t, 1).
1 + t2
We find the centre of the circle by moving a distance 1/k in the direction N
from (2), see formula on p. 8 which, when expressed in terms of t is:
1
c(t) = (t) + N(t)
k(t)
1
= (t, t2 /2) + (1 + t2 )3/2 (t, 1)
1 + t2
= (t3 , 1 + 3t2 /2). (1.5)

## So c(2) = (8, 6) and

(x + 8)2 + (y 6)2 = 53 .

## 6. (a) Show the curvature of a general curve (t) = (x(t), y(t)) is

0
x (t) y 00 (t) x00 (t) y 0 (t)

k(t) =
(x0 (t)2 + y 0 (t)2 )3/2
Stuck! I confirmed that this expression is correct using Wikepedia, but I
cant derive it.

6. (b) Show that the graph y = f (x) has the given curvature.
6

Here
(x) = (x, f (x)).
The unit tangent vector is found from the chain rule:
d(s)
T=
ds
d(x)/dx
=
ds/dx
(1.6)
To find the relation between arc length and x we note that (Boas, 1983,
Chapter 9):
p
ds = (dx)2 + (f 0 dx)2 ,
p
= 1 + f 02 dx.
p
ds/dx = 1 + f 02 . (1.7)
So the unit tangent vector is given by:
d(x)/dx
T(x) = ,
ds/dx
(1, f 0 )
=p . (1.8)
1 + f 02
And we use the chain rule again to find the curvature:

dT(s)
k= ds ,

dT(x)/dx
= ds/dx .

(1.9)
This gets a bit tedious, but is straightforward. Write T = (T x , T y ). The
x component is
dT x (1 + f 02 )1/2
= ,
dx dx
f 0 f 00
= . (1.10)
(1 + f 02 )3/2
Robs notes on Faber 7

## And a little algebra gives:

dT y f 0 (1 + f 02 )1/2
= ,
dx dx
f 00
= . (1.11)
(1 + f 02 )3/2
So
 x
dT dT y

dT(s) 1
= ,
ds ds/dx dx dx
f 0 f 00 f 00
 
1
=p , ,
1 + f 02 (1 + f 02 )3/2 (1 + f 02 )3/2
f 0 f 00 f 00
 
= , . (1.12)
(1 + f 02 )2 (1 + f 02 )2
And finally the curvature is the magnitude of this vector, which simplifies
to

dT(x)/dx
k=
,
ds/dx
f 00

=

02 3/2
. (1.13)
(1 + f )

## 6. (c) Compute the curvature of a semicircle

y = a2 x 2 .
From the part (b) above,
f 00

k=

02 3/2
. (1.14)
(1 + f )

Here f (x) = y = a2 x2 so
x
f0 = , (1.15)
a2 x 2
and
a2
f 000 = , (1.16)
(a2 x2 )3/2
8

## Fortunately this reduces to

f 00

k=
02 3/2
,
(1 + f )

2
a 1
= 2 ,

2
(a x2 )3/2 ( a2ax 2)
3/2
1
= , (1.17)
a
as it should since a was the radius of the semicircle.

7. Let
(t) = (a cos t, b sin t),
for 0 t 2, which defines an ellipse
x2 y 2
+ 2 = 1.
a2 b
Compute the curvature k(t) at t = 0 and t = /2 using the formula from
Exercise 6(a). Well need:
x(t) = a cos t,
x0 = a sin t,
x00 = a cos t.
and
y(t) = b sin t,
y 0 = b cos t,
y 00 = b sin t.
So
a
k(0) = , (1.18)
b2
b
k(/2) = 2 . (1.19)
a
Well need these later for solving Exercise I-2 problem 3.

## 8. This is clearly an important problem.

Robs notes on Faber 9

## 1.2 Gauss curvature (informal treatment)

The sign of the curvature is determined by the directions of the unit normal
to the curve U and the principal normal vector of the curve v known as
the normal section. But what is the principal normal vector.
Exercises I-2

1.3 Surfaces in E 3
Definition of surface involved a vector-valued function of two variables, X :
D E 3 , defined on an open subset D of <2 . Note that D is an open subset
of <2 . (D will be referred to in later sections without definition.)
Definition of regular on p. 22. In my words, amounts to being able to move
in 2 independent directions on the surface by changing the two parameters
(u, v). In Fabers words, p. 24, the regularity ensures that for each point of
and there is a continuous inverse function X() . So each point on
X() M has a unique set of coordinates (u, v).
Defines a tangent vector and tangent plane, denoted Tp M , on p. 26.

Exercises I-3

## X(u, v) = (f (u) cos v, f (u) sin v, g(u))

The tangent vectors are

X
X1 = = (f 0 (u) cos v, f 0 (u) sin v, g 0 (u))
u
X
X2 = = (f (u) sin v, f (u) cos v, 0) (1.20)
v
10

## As long as their cross-product

X1 X2 = (g 0 f cos v, g 0 f sin v, f 0 f )
(1.21)
is nonzero then have nonzero orthogonal components,
|X1 X2 |2 = (g 02 + f 02 )f 2 = 02 f 2
where
0 (u) = (f 0 , 0, g 0 )

## 1 (b). (i) uparameter curves.

Hold v = v0 fixed.
X(u, v0 ) = (f (u) cos v0 , f (u) sin v0 , g(u))
In the x z plane we see the original curve,
(u) = (f (u), 0, g(u))
but squished in the xdirection by cos v0 . In the y z plane its the same
curve but squished by sin v0 . In short, its like the curve (u) has been
rotated by v0 from the x z plane. The coordinates in the x z plane are
those of the shadow one would see if a light were shown through the curve
toward the x z plane. To obtain the y coordinates one shines the light
through the curve toward the y z plane.

## (ii) vparameter curves. Hold u = u0 fixed.

X(u0 , v) = (f (u0 ) cos v, f (u0 ) sin v, g(u0 ))
This is a circle at height x = g(u0 ) with radius f (u0 ).

## (iii) uparameter and vparameter curves intersect orthogonally.

The tangent vectors
X
X1 = = (f 0 (u) cos v, f 0 (u) sin v, g 0 (u))
u
X
X2 = = (f (u) sin v, f (u) cos v, 0) (1.22)
v
Robs notes on Faber 11

## point in the directions of the uparameter and vparameter curves. They

are orthogonal because
X1 X 2 = 0

2 (a). Sketch profile curve in x z plane and surface in 3D, show X, and
give equation for the surface in the form g(x, y, z) = 0.

## X(u, v) = (u cos v, u sin v, a u)

In the x z plane the curve is a straight line with slope one. The curves
form a cone with apex at the origin.
The tangent vectors are
X
X1 = = (cos v, sin v, a)
u
X
X2 = = (u sin v, u cos v, 0) (1.23)
v
Their cross-product

## X1 X2 = (au cos v, au sin v, u)

(1.24)

has magnitude
|X1 X2 |2 = u2 (1 + a2 )
so for u 6= 0, X is regular.
We can express the surface in the form g(x, y, z) = 0 by

a2 (x2 + y 2 ) z 2 = 0

## 3(a) Show that the helicoid (example 9) is a ruled surface.

Helicoid
X = (u cos v, u sin v, bv)
12

By inspection,
(v) = (cos v, sin v, 0)
so then
u(v) = (u cos v, u sin v, 0)
and we require
(v) = (0, 0, bv)
And thus we have expressed the helicoid surface in the form of a ruled surface:

X = (v) + u(v)

## 3(b) Show that the hyperbolic parabola (example 5) is a doubly ruled

surface.

Hyperbolic parabola:

X(u, v) = (u v, u + v, 2uv)

By inspection,
(u) = (1, +1, 2u)
so then
v(u) = (v, +v, 2uv)
and we require
(u) = (u, u, 0)
And thus we have expressed the helicoid surface in the form of a ruled surface:

X = (u) + v(u)

## Interchanging u and v in X(u, v) = (u v, u + v, 2uv) we see that we can

repeat the above argument to obtain:

X = (v) + u(v)

## so the hyperbolic parabola is doubly ruled.

Robs notes on Faber 13

## To show that it is regular we find the tangent vectors:

X1 = (1, 1, 2v)
X2 = (1, 1, 2u) (1.25)

## ||X1 X2 ||2 = ||2(u v, (u + v), 1)||2 = 4[(u v)2 (u + v)2 + 1] 6= 0

We should also confirm that these equations are indeed the hyperbolic parabola
of Example 5, which was expressed as
1
z = (y 2 x2 )
2
Substituting from X we find z = 2uv and
1 2 1
(y x2 ) = [(u + v)2 (u v)2 ] = 2uv = z,
2 2
confirming it is the hyperbolic parabola.

## 4. If = (u) is a smooth curve in E 3 and is a non-zero vector with

constant coefficients, then the ruled surface X(u, v) = (u) + v is called
a cylinder. (The special case of a right circular cylinder results when is a
circle and is perpendicular to the plane of .)

## (a) Show that X is regular except where 0 = 0. Describe the u

and v parameter curves.

## Clearly X1 = 0 and X2 = so,

X 1 X2 = 0

The surface will be regular when the tangent vectors are not parallel, which
means that X1 X2 6= 0.
The uparameter curves are given by (u), a general smooth function of
u producing a curve in E 3 .
The vparameter curves are given by (u0 )+v. These are straight lines
in the direction of the vector that pass through (u0 ).
14

## The uparameter curves are parabolae parallel to the x y plane. The

apex of the parabolae falls on the y z plane along the line z = 2y. The
vparameter curves are straight lines passing through the parabolae and are
parallel to z = 2y in the y z plane. The surface looks a bit like the hull
of a ship but it extends forever downward and upward.

7. Let (u) = (cos(u), sin(u), 0). Through each point of (u), pass a unit
line segment with midpoint (u) and direction vector
 u  u
(u) = sin (u) + cos (0, 0, 1)
2 2
The resulting surface,
1 1
X(u, v) = (u) + v(u), v
2 2
is called a Mobis strip!

## (7a) The coordinate functions:

u
x(u, v) = cos u + v sin cos u
2
u
y(u, v) = sin u + v sin sin u
2
u
z(u, v) = v cos (1.26)
2

## 1.4 The first fundamental form

p. 34. Middle of page, unfortunate notation: Any open subset of R2 may
serve as the domain of X. Here, R is not the larger radius of the torus, it
means R from Rn , the product space of ordered ntuplets of real numbers.
In fact, R2 was used on p. 22.
p. 35 Middle of page, typo: In the new rotation should be notation
not rotation.
Robs notes on Faber 15

Exercises I-4

1. Derive the formula ds2 + dr2 + r2 d2 for the differential of arc length
in polar coordinates by substituting

x = r cos y = r sin

into the formula ds2 = dx2 + dy 2 for the differential of arc length in Cartesian
coordinates.

x(r, ) x(r, )
dx = dr + d = cos dr r sin d
r
y(r, ) y(r, )
dy = dr + d = sin dr + r cos d (1.27)
r
Squaring and adding we find the cross terms cancel, leaving the desired result
ds2 + dr2 + r2 d2 .

2(a). L = 2(exp() exp())

2(b). L = 8a

3(a). Find (gij ), (g ij ), det (gij ), U, where U is the unit normal, for the

## X(u, v) = (R cos u cos v, R sin u cos v, R sin v)

The tangent vectors are:

## X1 = (R sin u cos v, R cos u cos v, 0)

X2 = (R cos u sin v, R sin u sin v, R cos v) (1.28)
16

## The metric tensor components are:

g11 = X1 X1 = R2 cos2 v
g12 = X 1 X2 = 0
g21 = g12 = 0
g22 = X 2 X2 = R 2 (1.29)

## Because the metric tensor is diagonal, the components of the inverse

metric tensor are simply the inverse of the diagonal coefficients of the metric
tensor (and zero in the off diagonal components):

g ij = 1/gij

The determinant is
det(gij ) = R4 cos2 v
The unit normal vector U is
X1 X 2
U=
||X1 X2 ||
R2 (cos u cos2 v, sin u cos2 v, cos v sin v)
=
||R2 (cos u cos2 v, sin u cos2 v, cos v sin v)||
= (cos u cos v, sin u cos v, sin v) (1.30)

5. Compute the metric form (or first fundamental form) and the unit
normal vector U for the general surface of revolution (Exercise 1, Section 3).

## The tangent vectors were

X
X1 = = (f 0 (u) cos v, f 0 (u) sin v, g 0 (u))
u
X
X2 = = (f (u) sin v, f (u) cos v, 0) (1.31)
v
Robs notes on Faber 17

The metric form (or first fundamental form) (see Eqs. 6 & 4 and p. 35) can
be written:
ds2 = g11 du2 + 2g12 du dv + g22 dv 2
with

g11 = X1 X1 = f 02 + g 02
g12 = X1 X2 = 0
g22 = X2 X2 = f 2 (1.32)

## For the unit normal vector,

X 1 X2 X1 X2
U= =p
||X1 X2 || det(gij )
(g f cos v, g f sin v, f 0 f )
0 0
= p
f f 02 + g 02
(g 0 cos v, g 0 sin v, f 0 )
= p (1.33)
f 02 + g 02

6(a). Show that the area A of the general surface of revolution (Exer-
cise 1, Section 3) between a u b and 0 v 2 is
Z b p
A = 2 f (u) f 0 (u)2 + g 0 (u)2 du
a

## Recall from Eq. (13),

dA = g du dv
2 Z b

Z
A= g du dv
0 a
Z 2 Z b p
= f f 02 + g 02 du dv
0 a
Z b p
= 2 f f 02 + g 02 du (1.34)
a
18

## Although X(u, v) : D E 3 where D was an open subset of <2 , (c.f. p. 22),

Eq. (13) was claimed to be valid for X(u, v) : E 3 with a closed subsets
of <2 , (c.f. top of p. 38), with X(u, v) being regular and one-to-one only on
the interior of .

6(b). Show that the area A of the surface obtained by revolving the
graph y = f (x), a x b about the xaxis is
Z b p
A = 2 f (x) 1 + f 0 (x)2 dx
a

## Consider a small element of this surface consisting of a circular ring about

the xaxis with radius f (x) and centred at x. Its area will be 2f (x)dl, where

## dl2 = dx2 + dy 2 = dx2 + f 02 dx2

p
thus dl = 1 + f 02 dx and
Z b Z b p
A = 2 f (x)dl = 2 f (x) 1 + f 0 (x)2 dx
a a

## 1.5 Second Fundamental Form

A strange and subtle thing happens after Faber introduced The Second Fun-
damental Form
0 0
Lij ui uj
on p. 44. He first tells us how to computer the coefficients, Lij in Eq. (20),
0 0
but then says nothing about ui uj . In principles, these should be familiar
0 dui
ui
ds
But their computation deserves at least a sentence or two. Then he works
through two examples, Example 13 and 14 on pp. 4446 and doesnt say
0 0
anything about ui uj . Heres my two cents on their computation. Lets go
back to the first fundamental form:

## ds2 = gij dui duj

Robs notes on Faber 19

## So if we suppress summation over repeated indices, we can write:

dui 1
=
ds gii
In the next section (I-6 on Gauss curvature) Faber will speak of the second
fundamental form as being just Lij . It will be explained in that section that
one can compute the Gauss curvature K using just the gij and Lij , see
Theorem I-5.

Exercises I-5
Most of these are straightforward computations. Exceptions are 1, 6, and
8. The first is quite easy. Here are my solutions for 6 and 8.

## 6. Prove Meusniers Theorem.

If one jumps in and starts computing the curvature of the surface etc.
without thinking through whats going on, one can quickly get lost in com-
plicated computations. (I know from personal experience!) On the other
hand if one understands Eqs. (16, 17, 18), then the answer if very obvious.
00 (s)
is the vector proportional to the curvature of the curve at point (s). It
00
can be projected onto the tangent plane of the surface giving tan and the
00
remainder projects onto the normal to the surface U giving nor , Eq. (14).
The curvature of the surface in the direction of the curve T(s) = 0 (s) is the
magnitude
00 0 0
||nor || = Lij ui uj
So Meusniers Theorem is essentially contained in Eq. (22)
0 0
kn (v) = Lij ui uj = 00 U = ||00 || cos
where v = 0 (s) is the direction of the curve at point s and is the angle
between 00 (s) and U, noting of course that U is a unit vector.
20

## 8. First try writing the unit normal vector U, see p. 33, as

x y z
1 1
U = X1 X2 = det x1 y1 z1
g g
x2 y2 z2

where we have used Eq. (10) on p. 35 relating the determinant of the matrix
g to the magnitude squared of X1 X2 . Here x is the unit vector in the
xdirection, and similarly for the other 2 directions in Euclidean space. Now
since Lij = Xij U (see Eq. (20) p. 44), its the xcomponent of Xij that
multiplies the x component of U. So we can simply replace the unit vectors
above with the corresponding components of Xij , giving the desired relation

xij yij yij
1
Lij = det x1 y1 z1
g
x2 y2 z2
Chapter 6

Extended Indices

## 6.1 Index of symbols

A smooth curve, see p. 1.

d(t)
0 (t)
dt
The derivative vector or velocity of the smooth curve parameterized
by t, see p. 2.

00 d2 (t)
(t)
dt2
The acceleration vector of the smooth curve parameterized by t, see
p. 4.

D
Open subset of R2 , see p. 22.

E3
Three dimensional Euclidean space, see p. 1.

21
22

k(s) = ||T0 (s)||
Curvature of a smooth curve at point (s).

T0 (s)
N(s) =
||T0 (s)||
Principal Normal vector, see p. 6.

s
Arc length of a smooth curve, see pp. 2, 3. Use as a parameter of the
curve, see p. 5.

t
Often used as a real parameter for the curve (t), not necessarily time
but clearly meant to imply that in some contexts.

T(s) = 0 (s)
Unit tangent vector, see p. 5.

T0 (s) = 00 (s)
Curvature vector, see p. 5.

Tp M
Tangent plane at point P of surface M. See pp. 26, 47.

U
Unit normal vector, p. 33,
Robs notes on Faber 23

## 6.2 Index of terms

Catenoid: p. 48, see also Exercise 2(f) of section I-3 on p. 28, and
Exercise 9(e) of Section I-6.

24

## 6.3 List of Definitions, Theorems, and Lem-

mas
1. Definition I-1: Curvature (of a curve in E3 ), pp. 5-6.

## 3. Definition I-3: Normal Curvature (of a surface in E3 in the direction of

a vector), p. 46.

## 4. Definition I-4: Principal Curves (of a surface in E3 ), principal directions

(of the corresponding curves), and Gauss curvature (of corresponding
surface) p. 49.

K(P) = L/g. p.50

## 6. Theorem I-6: p.54

U1 U2 = K(X1 X2 )

p. 58.

## 9. Theorem I-9: p. 65. Let = (s), a s b, be a curve on the

surface M, where s is arc length. If is the shortest possible curve on
M connecting its two end points, then is a geodesic.

10. Theorem I-10: p. 68. Given a point P of M and a unit tangent vector
v at P, there exists a unique geodesic (s) such that (0) = P and
0 (0) = v.
Bibliography

## Boas, M. L., 1983: Mathematical methods in the physical sciences. John

Wiley and Sons, 793 pp.

## Faber, R. L., 1983: Differential geometry and relativity theory: An Introduc-

tion. Marcel Dekker. 255 + X pp.

25